Coaching novice swimmers freestyle and backstroke - Malone, P. (American Swimming ASCA Newsletter, 1997)
Tipps for coaching novice swimmers freestyle and backstroke (body position, balance, kick, armstroke, breathing, recovery). Five tips to become a S.U.P.E.R. Novice Coach: - S_Show and Tell - U_Useful Information - P_Praise - E_Enthusiasm - R_Repetition